Scientific advice to governments: Palgrave Communications - Editors (New Zealand Science Review, 2016)
A collection of 12 articles, build on the conclusions of the first Science Advice to Governments conference in Auckland in August 2014, which led to the creation of International Network for Government Science Advice (INGSA)Scientific advice to governments has never been in greater demand; nor has it been more contested. From climate change to cyber-security, poverty to pandemics, food technologies to fracking, the questions being asked of scientists, engineers and other experts by policymakers, the media and the wider public continue to multiply and increase in complexity. At the same time, the authority and legitimacy of experts are under in-creasing scrutiny, particularly on controversial topics, such as climate change and genetically modified crops. This thematic collection (‘special issue’) brings together perspectives on the theory, practice and politics of scientific advice from a range of disciplines and countries, including Canada, China, Japan, Netherlands, Nigeria, the US and UK. The guest editors of this collection, Prof Sir Peter Gluckman, Chief Science Advisor to the Prime Minister of New Zealand, and Prof James Wilsdon, Professor of Research Policy, Faculty of Social Sciences, University of Sheffield, UK, hope that new papers will continue to be added to this collection, making it a living, fully open access repository for new scholarship and policy thinking – and an important contribution to the emerging science and art of scientific advice.